Genetic Association Studies in Uterine Fibroids: Risk Alleles Presage the Path to Personalized Therapies - Gallagher, C. Scott; Morton, Cynthia C. (Seminars in Reproductive Medicine, 2016)
Uterine leiomyoma (UL) is the most common tumor of the female reproductive system. Epidemiological analyses, including familial aggregation, twin studies, and racial discrepancies in disease prevalence and morbidity, indicated genetic factors influence risk for developing UL. Genome-wide association studies (GWASs) are a powerful method for identifying genetic variants that are associated with elevated risk for a common, complex disease. To date, three genome-wide scans for UL have been performed: a GWAS in Japanese women, a genome-wide linkage and association study in women of European decent, and an admixture-based analysis in African American women. Results from each of the three genome-wide scans performed have had varying success in identifying unique loci associated with predisposition to developing UL. Here, we address the evidence for a genetic basis for UL risk, discuss genetic association studies and their results, and identify challenges and future directions for UL GWAS analyses.
Keywords: uterine leiomyomata; genetic association; complex diseases